Structural responses to the obesity epidemic in Latin America: what are the next steps for food and physical activity policies? - Grace Melo; Nicolas Aguilar-Farias; Emiliano López Barrera; Laura Chomalí; María Alice Moz-Christofoletti; Juan Carlos Salgado; Luana Joppert Swensson; Juan Carlos Caro (Elsevier, 2023)
Summary: Obesity is among the most complex public health challenges, particularly in Latin America, where obesity rates have increased faster than in any other region. Many countries have proposed or enacted comprehensive policies to promote adequate diet and physical activity under a structural framework. We summarize articles discussing the scope and impact of recently implemented obesity-related interventions in the light of a structural response framework. Overall, we find that: (1) market-based food interventions, including taxes on junk food, nutrition labelling, and marketing restrictions, decrease the consumption of targeted foods, (2) programs directly providing healthy foods are effective in reducing obesity, and (3) the construction of public areas for recreation increases the average frequency of physical activity. Although obesity-related interventions in the region have somewhat improved health behaviours, obesity prevalence remains on an upward trend. We discuss some opportunities to continue tackling the obesity epidemic in LATAM under a structural framework.